Analysis of Bank Health on Profit Growth in New Normal Conditions with CAMELS Method at BPR Syariah in East Java - DURA, Justita; CAHYANINGTYAS, Fadilla (Journal of Tourism Economics and Policy, 2021)
Assessment of various aspects that affect the performance of a bank through other factors, among others, Asset Quality, Management, Earning, Liquidity, and Sensitivity to Market Risk is the health of the bank. The purpose of this study was to determine the effect of bank health on new normal profit growth at BPR Syariah East Java in 2020. The research method used in this research is multiple linear regression analysis method. The type of data used in this study is quantitative and the data sources used are included in secondary data. The results of the study of capital have no influence on profit growth, asset quality has no influence on profit growth, management has no influence on profit growth, income has no influence on profit growth, liquidity has no influence on profit growth, and sensitivity to market risk has no influence on profit growth.